Nip allergies in the Bub: a qualitative study for a public health approach to infant feeding for allergy prevention. (26th May 2022) - Vale, Sandra L.; Roche, Ingrid; Netting, Merryn; Said, Maria; Joshi, Preeti; Clifford, Rhonda; Campbell, Dianne E.; Salter, Sandra M.
Abstract: Objective: To identify a brand, key messages and resources to underpin a public health approach to food allergy prevention. Methods: A focus group design was used to explore perceptions and opinions of potential brands, infant feeding messages and resources for providing standardised food allergy prevention information. Focus groups were conducted in February 2018 using interview guides and were transcribed verbatim. A content analysis of the transcripts was undertaken using thematic analysis software. The University of Western Australia provided ethics approval: RA/4/20/4280. Results: Seven focus groups with 39 participants were conducted. Four slogans and styles of imagery were considered. 'Nip Allergies in the Bub' was the most favoured slogan and images of babies with food were most favoured. Participant feedback was sought regarding messages and supporting messages were considered important. Participants were consulted about useful resources and a website was identified. Conclusions: Conducting focus groups assisted the selection of a brand, messages and resources to underpin a public health approach to implementing allergy prevention guidelines. Implications for public health: This is the first focus group research undertaken for food allergy prevention. Identification of a meaningful brand, key messages and resources will support a public health approach to implementing allergy prevention guidelines.